Effects and safety of extracorporeal membrane oxygenation in the treatment of patients with ST-segment elevation myocardial infarction and cardiogenic shock: A systematic review and meta-analysis - Pang, Shuo; Miao, Guangrui; Zhao, Xiaoyan (Frontiers in Cardiovascular Medicine, 2022)
Background There is a lack of large RCTs that comprehensively evaluate the effects of extracorporeal membrane oxygenation (ECMO)- assisted treatment of patients with ST-segment elevation myocardial infarction (STEMI) combined with Cardiogenic shock (CS). This meta-analysis aims to identify mortality, predictors of short-term mortality, and the incidence of various complications in patients with STEMI and CS treated with ECMO. Methods We meta-analyzed mortality, risk factors of mortality, and complications of patients with STEMI and CS treated with ECMO from systematically selected studies published from 2018 to January 2022. Results 15 studies (1144 patients) were included with a pooled mortality estimate of 51.0% mortality. Age>65 years, BMI >25 kg/m2, lactate >8 mmol/L, anterior wall infarction, longer CPR time, and longer time from arrest to ECPR were risk predictors of mortality. Achieving TIMI-3 flow after PCI was a protective factor of mortality. The prevalence of bleeding, cerebral infarction, leg ischemia, and renal failure were 0.22, 0.099, 0.074, and 0.383, respectively. Conclusion These results can help clinicians develop new mortality prediction models and select patients who are most likely to benefit from ECMO support by balancing the benefits and risks.